Demokratisasi Internal Partai Politik Era Reformasi: Antara Das Sollen dan Das Sein - Jamaludin Ghafur (Fakultas Hukum Universitas Islam Indonesia, 2023)
Political parties as the main feature of representative democracy may only be able to function optimally in upholding the principles of democratic government if they are managed internally in a democratic manner. It is impossible for a democratic program to be developed by a non-democratic political party. This paper aims to comprehensively analyze the development of arrangements and practices of internal democratization of political parties in Indonesia during the reform era, especially in the context of leadership succession. This is a doctrinal legal research using primary, secondary and non-legal sources of law. The most important finding from this research is that the rules regarding the internal democratization of political parties are still very general and abstract, giving rise to many interpretations. In addition, there are no provisions for strict sanctions against political parties that do not heed these rules. As a result, most political parties often ignore orders or obligations to carry out the succession of their leaders in a democratic manner as mandated by law.Key Words: Internal democratization of political parties; leadership succession; reform era AbstrakPartai politik sebagai fitur utama demokrasi perwakilan hanya mungkin dapat berfungsi maksimal dalam menegakkan prinsip-prinsip pemerintahan yang demokratis jika secara internal dikelola secara demokratis. Sebuah program demokratis tidak mungkin bisa dikembangkan oleh partai politik yang tidak demokratis. Tulisan ini ingin menganalisis secara komprehensif perkembangan pengaturan dan praktik demokratisasi internal partai politik di Indonesia era reformasi, khususnya dalam konteks suksesi kepemimpinan. Penelitian ini merupakan penelitian hukum doktrinal dengan menggunakan sumber-sumber hukum primer, sekunder dan sumber non-hukum. Temuan terpenting dari penelitian ini adalah bahwa aturan tentang demokratisasi internal partai politik masih sangat umum dan abstrak sehingga menimbulkan banyak interpretasi. Selain itu, tidak ada ketentuan sanksi yang tegas terhadap partai politik yang tidak mengindahkan aturan tersebut. Akibatnya, sebagian besar partai politik seringkali mengabaikan adanya perintah atau kewajiban untuk melaksanakan suksesi kepemimpinnya secara demokratis sebagaimana diamanatkan oleh undang-undang. Kata-kata Kunci: Demokratisasi internal partai politik; suksesi kepemimpinan; era reformasi